To view or not to view: Examining the plain view doctrine and digital evidence - Moore, Robert (American journal of criminal justice, 2004)
The very nature of digital evidence, defined as evidence stored on any form of magnetic media, makes the proper collection of such evidence an important consideration during seizure. Historically, courts have attempted to apply jurisprudence developed for the physical world to cases involving the cyber world. As a result, confusing guidelines have been created for those who handle computerrelated investigations. This article examined the issue of warrantless searches and seizures of digital evidence justified under the plain view doctrine. Through examination of the Fifth Circuit decision, United States v. Carey (1999), and the Virginia district court decision, United States v. Gray (1999), it was determined that proper seizure of digital evidence under the plain view doctrine requires: 1) access to the evidence be obtained legally, 2) the apparent illegal nature of the evidence be immediately known, and 3) the officer cannot abandon their original search.